Traduire He-Yin Zhen, perspectives sur la circulation des idées féministes - Léa Buatois (Glad!)
This article proposes the unpublished translation of excerpts from texts and articles written by the Chinese anarchist and feminist theorist He-Yin Zhen (1884-v.1920), as well as an attempt to rebuild a complete list of her works. Re-discovering and translating these texts does raise many questions. Is translation already interpretation? How can we account for the history of the concepts and words she uses and their transformations throughout time? What do these texts have to say about the history of feminism ? What do they teach us about knowledge production on Chinese history or in the area of « Chinese Studies » ? Can translation be a tool for the ongoing feminist struggles, or does it reinforce the colonial structures of knowledge?